Analisis Faktor-Faktor yang Mempengaruhi Tingkat Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus KPP Pratama Malang Utara) - Apriansyah, Ikhwan; Afifudin, Afifudin; Hidayati, Irma (Universitas Islam Malang, 2024)
Tax is Indonesia's main source of income used to finance state interests, including development. Due to the increasing development costs, the government is trying to maximize tax revenues, which greatly affect the state budget. This study aims to examine the effect of tax knowledge, tax rates, service quality, and tax sanctions on individual taxpayer compliance, with sampling using the Slovin formula. This study uses a quantitative method by distributing questionnaires to 100 taxpayers registered at the Malang Utara Pratama Tax Office. The results of this study explain that tax knowledge, tax rates and tax sanctions have a positive effect on individual taxpayer compliance, while service quality does not affect individual taxpayer compliance. It is hoped that this study can be a consideration for related parties to improve knowledge, rates, service quality and sanctions on individual taxpayer compliance.Keywords : Tax knowledge, tax rates, service quality, tax sanctions, taxpayer compliance.